A female infant with phacomatosis pigmentovascularis and congenital chylous ascites: A case report. Issue 34 (August 2018) - Xu, Shuai; Zhang, Qinming; Liu, Tingting; Zhang, Ye; Sun, Ning
Abstract: Rationale: Phacomatosis pigmentovascularis (PPV) is a rare syndrome characterized by capillary malformation and pigmentary nevus. Congenital chylous ascites (CCA) is also a rare disease that results from maldevelopment of the lymphatic system. We report a case of a 5-month-old girl, who had both PPV and CCA. Patient concerns: A 5-month-old girl is reported, who presented extensive nevus flammeus and an aberrant Mongolian spot with congenital chylous ascites. Diagnoses: The expression of extensive nevus flammeus and an aberrant Mongolian spot with congenital chylous ascites, that was diagnosed as type IIb phacomatosis pigmentovascularis. Interventions: Conservative treatment included administration of somatostatin, MCT-based diet or TPN with drainage of ascitic fluid. Surgery was taken into account after failed conservative treatments. Before surgery, it is necessary to locate the abnormal lymphatic vessels. Outcomes: Conservative treatment and surgery sometimes functioned limitedly on CCA. Lessons: According to the classification system of ISSVA (the International Society for the Study of Vascular Anomalies), this case meet the classification of CLM included in combined vascular malformations. It is likely to there is a connection between these two congenital diseases.